2023
DOI: 10.3390/fib11110092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkali Treatment under Ambient and Heated Conditions on the Physicochemical, Structural, Morphological, and Thermal Properties of Calamus tenuis Cane Fibers

Arup Kar,
Dip Saikia,
Sivasubramanian Palanisamy
et al.

Abstract: This study explores the effect of alkali treatment at ambient (25 °C) and elevated temperatures (100 °C) on the physicochemical, structural, morphological, and thermal properties of Calamus tenuis cane fibers (CTCFs) for the first time. Our purpose is to investigate their potential use as reinforcement in polymer composites, since cane fibers are generally known for their accurate and consistent geometrical orientation. Treatment with 8% (w/v) sodium hydroxide (NaOH) is carried out at ambient temperature and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Extensive research studies have provided detailed information on the chemical treatments used for reinforcement fibers and the improvement of the fiber adhesion properties of the matrix. [12,[52][53][54][55][56]…”
Section: Conventional Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research studies have provided detailed information on the chemical treatments used for reinforcement fibers and the improvement of the fiber adhesion properties of the matrix. [12,[52][53][54][55][56]…”
Section: Conventional Techniquesmentioning
confidence: 99%
“…Surface modification of plant fibers can improve surface roughness and reduce moisture absorption. [8][9][10][11][12] Various techniques [14][15][16] have been employed to enhance the compatibility between plant fibers that have water-absorbing properties and polymer materials that lack water absorption. Chemical surface treatments commonly employed for plant fibers encompass a range of techniques, including mercerization, [17][18][19][20][21] silylation, [22][23][24][25] acetylation, [26][27][28] benzoylation, [13,29,30] maleated coupling agents, [13,29,31] isocyanate treatment, [32] and transfer of synthetic polymers through grafting.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid fiber combination of glass and sisal with epoxy resin showed better results at overall wt% of 40 (Ramamoorthy et al 2015;Junaedi et al 2023). Hybrid natural fiber combination observed better mechanical properties due to better distribution of fibers in matrix with good adhesion of fiber with matrix phase (Arthanarieswaran et al 2014;Karuppiah et al 2022;Kar et al 2023;Palanisamy et al 2023b). It was observed that increasing the fiber percentage and adding nano clay particles to an epoxy/glass composite improved the tensile characteristics.…”
Section: Introductionmentioning
confidence: 92%
“…4, an optimal energy absorber achieves a CFE of 100%, indicating parity between mean and peak crushing forces. Collectively, these technical indicators furnish a comprehensive framework for the meticulous assessment and comparative analysis of crashworthiness characteristics in materials and structures, which are crucial for ensuring optimal performance and safety in diverse engineering applications (Kar et al 2023).…”
Section: Crashworthiness Indicatorsmentioning
confidence: 99%